2014
DOI: 10.1007/s00265-014-1861-1
|View full text |Cite
|
Sign up to set email alerts
|

Level of experience modulates individual foraging strategies of an invasive predatory wasp

Abstract: Spatiotemporal variation in access to resources modulates foraging behavior. Because flexible foraging and subsequent shifting niches can have cascading effects on food webs, it becomes critical to understand what and how information is used during foraging. Yellowjackets are efficient foragers, quickly relocating rewarding resources. Foraging context and the degree of experience were found to affect subsequent behavior and foraging success. An individual forager's likelihood of relocation was highest for carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 62 publications
0
17
0
Order By: Relevance
“…A similar pattern was found in Vespula pensylvanica wasps when landmarks were displaced during their relocating behaviour. Their flights were directed to the displaced landmarks but then were reoriented to the food source (Wilson‐Rankin ).…”
Section: Discussionmentioning
confidence: 99%
“…A similar pattern was found in Vespula pensylvanica wasps when landmarks were displaced during their relocating behaviour. Their flights were directed to the displaced landmarks but then were reoriented to the food source (Wilson‐Rankin ).…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies suggest that recruitment tends to take place at the nest [ 29 ]. Interestingly, Wilson-Rankin [ 51 ] found that twice as many Vespula pensylvanica wasps foraged on chicken baits when all foragers were allowed to return to the nest, compared to when visitation was restricted to naïve wasps only. However, in the present study with V. germanica , when all foragers were allowed to forage on the bait and return to the nest, the arrival pattern was exponential and the number of wasps was approximately 4 times greater than when no communication was allowed.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies and this study demonstrated that hornets can learn to associate food with certain visual, spatial and olfactory cues. This leads to successful foraging experiences, which obviously increase foraging efficiency (Monceau et al ., ; Wilson‐Rankin, ; Moreyra et al ., ). Hornets appear to learn attractive cues from diaspores and develop a search image for other diaspores of the same species, assuring highly effective seed dispersal for S. tuberosa .…”
Section: Discussionmentioning
confidence: 99%